Integrated CAD/CAM Approach for Experimental Stands in Hydrogen Explosion Analysis - Munteanu Laurentiu; Suvar Marius Cornel; Morar Marius; Miclea Olga; Pasculescu Adina Cristina (MATEC Web of Conferences, 2024)
Hydrogen is considered a promising clean energy carrier gas for the future and is used in fuel cell systems to generate electricity without producing greenhouse gas emissions. However, the safe storage and handling of hydrogen are essential for the widespread adoption of hydrogen as an alternative energy source. Research into hydrogen explosions is aimed at developing safe storage methods, safety guidelines, and accident prevention measures - crucial objectives for the sustainable growth of the hydrogen economy. Fundamental research into fast hydrogen combustion requires specially designed and built experimental stands to ensure both safe operation and recording of explosion parameters. More than a simple combustion chamber, often the geometry of the stands must contain elements to increase the complexity of the explosion process. In this respect, this paper deals with the possibilities of designing and 3D printing obstacles that can be placed in the path of hydrogen explosions on research stands to modify the cross-section, direct the pressure waves, turbulence the fluid movements, or even suppress the flame front. By combining the computer-aided modeling and design facilities offered by the Autodesk Fusion 360 software, digitized models are converted into 3D objects by the process of dividing them into thin horizontal layers (slices) and transmitting the information thus generated to the 3D printer, using Ultimaker Cura. Here, through the process of material deposition and fusion (FDM), the thermoplastic material is extruded, deposited layer by layer, rapidly cooling, and solidifying to form the final object.